Competitiveness of Indonesia’s Gambier Exports in the Indian Market: A VECM Analysis - Hasnah, Hasnah; Syafitri, Deolsha; Analia, Devi (Universitas Andalas, 2026)
This study aims to: (1) describe the development of Indonesia’s gambier exports, (2) assess the competitiveness of Indonesian gambier exports in the Indian market, and (3) identify the factors influencing this competitiveness (HS Code 320190). A quantitative approach is employed using time-series data from 1999 to 2024, obtained from Statistics Indonesia (BPS), the International Trade Centre (ITC), UN Comtrade, and Bank Indonesia. Export competitiveness is measured using the Revealed Comparative Advantage (RCA) index, while its determinants are analyzed using a Vector Error Correction Model (VECM). The findings show that Indonesia’s gambier exports to India have fluctuated over time but display a long-term upward trend. The RCA values consistently exceed one and fall within the category of strong comparative advantage (RCA > 4), indicating a high level of competitiveness. In fact, the RCA values range from approximately 21.23 to 38.25, demonstrating Indonesia’s dominant position as the primary supplier of gambier in the Indian market. The VECM results reveal that, in the long run, export volume, Indonesian gambier export prices, global gambier export prices, export prices of competing countries (Italy and Singapore), and the exchange rate significantly affect export competitiveness. In contrast, short-run adjustments toward equilibrium occur relatively slowly.